Building a career through growth mindset and grit: a study of organization students - Maharani, Mutiara; Erlin, Nia Ariyani (Institute of Computer Science (IOCS), 2025)
Career adaptability has emerged as an important competency in today’s dynamic and unpredictable work environment. Many university students still face considerable challenges in developing the flexibility and perseverance required to respond effectively to complex and evolving career demans in a competitive global marketplace. This research examines how a growth mindset impacts individuals' ability to adapt to their careers, with grit positioned as a mediating variable, with a focus on students who actively participate in student organizations at the Faculty of Economics and Business, Padang State University. A quantitative method was employed, utilizing data gathered from a structured questionnaire distributed to 110 respondents selected using probability sampling techniques. The data were processed using Structural Equation Modeling (SEM-PLS) with the assistance of SmartPLS version 4.0 software. The findings showed that growth mindset significantly influenced career adaptability, with grit as a mediating factor. The results of this study highlight the value of promoting a growth-oriented mindset and persistence in a organizational context to improve students overall career readiness, adaptability, personal development, and resilience in the future workplace.